2023
DOI: 10.1021/jacs.2c10763
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Takeoff of Single Sulfur Nanoparticles during Sublimation Studied by Dark-Field Microscopy

Abstract: The Leidenfrost effect describes a fascinating phenomenon in which a liquid droplet, when deposited onto a very hot substrate, will levitate on its own vapor layer and undergo frictionless movements. Driven by the significant implications for heat transfer engineering and drag reduction, intensive efforts have been made to understand, manipulate, and utilize the Leidenfrost effect on macrosized objects with a typical size of millimeters. The Leidenfrost effect of nanosized objects, however, remains unexplored.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Dark-field optical microscopy (DFM) obliquely illuminates particles to generate elastic scattering of light, which prevents the incident light from entering the objective, resulting in a dark background . DFM allows for acquiring high-quality color images with significant contrast and excellent sensitivity, making it suitable as a versatile and powerful tool for real-time monitoring of various chemical reactions at a single-particle level. For a long time, DFM is mainly limited to chemically imaging single plasmonic nanoparticles (Au, Ag, and doped semiconductor nanomaterials) due to their strong light-scattering capacity . Recently, we have demonstrated that the scattering light is sensitive to the alteration in the optical absorption and mass of single MOFs, realizing single-particle imaging of iodine adsorption and thermal dehydration processes on MOFs. , …”
Section: Introductionmentioning
confidence: 99%
“…Dark-field optical microscopy (DFM) obliquely illuminates particles to generate elastic scattering of light, which prevents the incident light from entering the objective, resulting in a dark background . DFM allows for acquiring high-quality color images with significant contrast and excellent sensitivity, making it suitable as a versatile and powerful tool for real-time monitoring of various chemical reactions at a single-particle level. For a long time, DFM is mainly limited to chemically imaging single plasmonic nanoparticles (Au, Ag, and doped semiconductor nanomaterials) due to their strong light-scattering capacity . Recently, we have demonstrated that the scattering light is sensitive to the alteration in the optical absorption and mass of single MOFs, realizing single-particle imaging of iodine adsorption and thermal dehydration processes on MOFs. , …”
Section: Introductionmentioning
confidence: 99%